Investing to build sustainable and resilient food systems under climate change - Wiebe, Keith (2016)
Keith Wiebe, IFPRI Food Security and Climate Change: How to build Sustainable and Resilient Food Systems OCP Side Event to COP22 Marrakech, Morocco